Quantifying Absolute Neutralization Titers against SARS-CoV-2 by a Standardized Virus Neutralization Assay Allows for CrossCohort Comparisons of COVID-19 Sera - Oguntuyo, Kasopefoluwa (2021)
The global coronavirus disease 2019 (COVID-19) pandemic has mobilized efforts to develop vaccines and antibody-based therapeutics, including convalescent-phase plasma therapy, that inhibit viral entry by inducing or transferring neutralizing antibodies (nAbs) against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike glycoprotein (CoV2-S). However, rigorous efficacy testing requires extensive screening with live virus under onerous biosafety level 3 (BSL3) conditions, which limits high-throughput screening of patient and vaccine sera. Myriad BSL2-compatible surrogate virus neutralization assays (VNAs) have been developed to overcome this barrier. Yet, there is marked variability between VNAs and how their results are presented, making intergroup comparisons difficult. To address these limitations, we developed a standardized VNA using CoV2-S pseudotyped particles (CoV2pp) based on vesicular stomatitis virus bearing the Renilla luciferase gene in place of its G glyco-protein (VSVDG); this assay can be robustly produced at scale and generate accurate neutralizing titers within 18 h postinfection. Our standardized CoV2pp VNA showed a strong positive correlation with CoV2-S enzyme-linked immunosorbent assay (ELISA) results and live-virus neutralizations in confirmed convalescent-patient sera. Three independent groups subsequently validated our standardized CoV2pp VNA (n . 120). Our data (i) show that absolute 50% inhibitory concentration (absIC50), absIC80, and absIC90 values can be legitimately compared across diverse cohorts, (ii) highlight the substantial but consistent variability in neutralization potency across these cohorts, and (iii) support the use of the absIC80 as a more meaningful metric for assessing the neutralization potency of a vaccine or convalescent-phase sera. Lastly, we used our CoV2pp in a screen to identify ultrapermissive 293T clones that stably express ACE2 or ACE2 plus TMPRSS2. When these are used in combination with our CoV2pp, we can produce CoV2pp sufficient for 150,000 standardized VNAs/week. IMPORTANCE Vaccines and antibody-based therapeutics like convalescent-phase plasma therapy are premised upon inducing or transferring neutralizing antibodies that inhibit SARS-CoV-2 entry into cells. Virus neutralization assays (VNAs) for measuring neutralizing antibody titers (NATs) are an essential part of determining vaccine or therapeutic efficacy. However, such efficacy testing is limited by the inherent dangers of working with the live virus, which requires specialized high-level biocontainment facilities. We there-fore developed a standardized replication-defective pseudotyped particle system that mimics the entry of live SARS-CoV-2. This tool allows for the safe and efficient measurement of NATs, determination of other forms of entry inhibition, and thorough investigation of virus entry mechanisms. Four independent labs across the globe validated our standardized VNA using diverse cohorts. We argue that a standardized and scalable assay is necessary for meaningful comparisons of the myriad of vaccines and antibody-based therapeutics becoming available. Our data provide generalizable metrics for assessing their efficacy.